The World Atlas of Deserts and Drylands - David Thomas; Sternberg, Troy; Sallie Burrough; Nicholas Drake; Marion Meyer (2025)
Deserts and drylands account for more than 40 percent of land on our planet. Characterized by a lack of water and extreme temperatures, they are the result of atmospheric stability, large landmass characteristics, rain shadows, and cold ocean currents. They appear harsh and hostile, but deserts and drylands are also exceptionally beautiful environments. Desert ecosystems often teem with diverse forms of life that exhibit astonishing ingenuity in the face of such forbidding conditions. The World Atlas of Deserts and Drylands takes readers on a guided tour of some of the most awe-inspiring desert environments on Earth, explaining their environmental and ecological dynamics and describing the techniques used to categorize and map them. From the ever-expanding Gobi of Mongolia and China to the ancient Namib of coastal Africa, this is the ultimate reference book for deserts.